The Role of Social Media and User-Generated Content in Traveler Decisions: A Literature Review - Al Fajar, Adam Hafidz; Dyas Erlangga (Journal of Tourism and Creativity, 2025)
This study aims to explore the role of social media and user-generated content (UGC) in influencing traveler decision-making processes in the digital era. Using a qualitative approach through a literature review method, this research systematically analyzes studies published in the last ten years sourced from Scopus and Google Scholar databases. Specific keywords such as “social media and tourist decision-making,” “user-generated content and travel behavior,” and “digital word of mouth and tourism” were used to collect relevant literature. The findings reveal that social media and UGC play a significant role across three stages of the travel process: pre-trip, during the trip, and post-trip. In the pre-trip stage, UGC serves as a primary source of inspiration and information, forming travelers’ initial perceptions of destinations. During the trip, travelers rely on real-time content to make decisions, while post-trip experiences shared online influence the future choices of other travelers. Factors such as perceived risk, content credibility, self-actualization, and social validation further strengthen UGC’s impact. Overall, the study concludes that UGC and social media are not just supplementary sources but central elements in modern travel decision-making. Understanding their role is crucial for stakeholders to develop effective and sustainable digital tourism strategies